Humoral and cellular immune response generated by different vaccine programs before and after Salmonella Enteritidis challenge in chickens - Casarin Penha Filho, Rafael Antonio [UNESP]; Moura, Bruna Silva [UNESP]; de Almeida, Adriana Maria [UNESP]; Montassier, Helio Jose [UNESP]; Barrow, Paul A.; Berchieri Junior, Angelo [UNESP] (Elsevier B.V., 2012)
The poultry industry has a high demand for Salmonella vaccines in order to generate safer Salmonella-free food for consumers around the world. Vaccination against S. Enteritidis (SE) is vastly undertaken in many countries, although the criteria for the use of live vaccine (LV) or killed vaccine (KV) should also depend on the immune mechanisms triggered by each. In this study, a commercial bacterin (KV) and an attenuated SG mutant (LV) were used in four different vaccine programs (LV; LV+LV; KV; LV+KV). At 1 day before (dbi) and 1, 6 and 9 days after SE challenge (dpi), humoral (IgM, IgG and secretory IgA) and cellular (CD8(+) T cells) immune responses were evaluated along with the production of IL-10, IL-12 and IFN-gamma. Although after challenge, all birds from each group had an influx of CD8(+) T cells, birds which received KV had lower levels of these cells in organs and significantly higher levels of immunoglobulins. The expression of the cytokines was up-regulated in all groups post-vaccination, although, after challenge, cytokine expression decreased in the vaccinated groups, and increased in the unvaccinated group A. IL-10 levels were significantly higher at 1 day post-infection in the group that received KV, which may be involved in the weak cellular immune response observed within this group. In caecal tonsils, IFN-gamma expression at 1 dbi was higher in birds which received two vaccine doses, and after challenge, the population of CD8(+) T cells constantly increased in birds that were only vaccinated with the LV. This study demonstrated that the development of a mature immune response by CD8(+). T cells, provided by the use of the LV, had better efficacy in comparison to the high antibody levels in the serum stimulated by the KV. However, high secretory IgA levels in the intestinal lumen associated with influx CD8(+) T cells may be indicative of protection as noticed in group E (LV+KV). (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: salmonellosis; Cytokine; Immunoglobulins; CD8(+) T cells; ELISA